Women and LGBTQI people in the Catholic Church: hints of liberation - Lawler, Michael G. (Theology & sexuality, 2026)
Liberation theology is well-known and well-established in the twenty-first century. It was born in the 1960s in a Latin American context as a protest of Catholic faith against the widespread social and economic oppression and suffering of that region’s poor. It is not to be so restrictively understood in this essay; here it is extended to be understood of the ‘human poverty,’ the deprivation of human dignity, of women and LGBTQI individuals. In this essay we do not offer any full treatment of liberation theology. We argue only that, in the words of Pope John Paul II, it is useful and necessary throughout the world, not only for the world’s poor but also for the women and LGBTQI individuals made poor in human dignity in and by the Catholic Church.